How do you simplify 2x +5(6x-4)+ 12x+5(6x−4)+1? Algebra Expressions, Equations, and Functions Variable Expressions 1 Answer MeneerNask Jul 6, 2015 You first get rid of the brackets Explanation: =2x+5*6x+5*(-4)+1=2x+5⋅6x+5⋅(−4)+1 =2x+30x-20+1=2x+30x−20+1 =32x-19=32x−19 Answer link Related questions How do you write the variable expression for: a quotient of 2 and the sum of a number and 3 ? What are variables? What are variable expressions? How do you write variable expressions? How do you evaluate variable expressions? How do you simplify the expression 3x-x+43x−x+4? How do you write a quotient of a number and 6 as an expression? How do you evaluate the expression 2x+12x+1 for x=1x=1? How do you write a product of a number and 2 as an expression? How do you write 5 less than 2 times a number as a variable expression? See all questions in Variable Expressions Impact of this question 1374 views around the world You can reuse this answer Creative Commons License